Theoretical aspects of creating electronic teaching tools for life safety for primary school children - Zakalinskaya, Карина Викторовна; Surikov, Андрей Валерьевич; Zaynudinova, Наталья Владимировна (Journal of Civil Protection, 2025)
Purpose. To study the theoretical aspects of creating electronic learning tools for children of primary school age, including psychological and pedagogical features and distinctive features of gamification in education, as well as the influence of electronic devices on the development of children of this age group, and to determine the main approaches to the design of the specified methodological support. Methods. The general research methodology included the use of theoretical research methods (analysis and synthesis) and the sociological method of obtaining information. Findings. A review and analysis of scientific and literary sources devoted to the psychological and pedagogical features and distinctive features of gamification in education, as well as the influence of electronic devices on the development of primary school children is conducted. The results of the study of the opinions of parents of primary school children on the use of electronic devices in the lives of their children are presented. The main approaches to the design of electronic learning tools intended to develop a culture of life safety in primary school children are defined. Application field of research. The obtained research results can be applied in the design and creation of electronic means of teaching primary school children life safety issues.